Advancing Tourism Through Green Accounting in Culinary Waste Management Bangsal Beach, Sanur - Ni Made Ayu Maya Puspita; Ni Made Sintya Surya Dewi; Putu Esa Naranata Dewi (Juara: Jurnal Riset Akuntansi, 2026)
This study aims to evaluate the effect of green accounting implementation on waste management among culinary businesses in the coastal area of Bangsal Beach, Sanur, Denpasar, in supporting green tourism. This study employed a quantitative approach using a survey method. The research sample consisted of 102 respondents selected through purposive sampling from 34 culinary business units. The data were analyzed using simple linear regression. The results show that green accounting has a positive and significant effect on waste management. The Adjusted R² value of 0.738 indicates that green accounting explains 73.8% of the variation in waste management, while the remaining variation is explained by other factors outside the research model. These findings confirm that integrating environmental costs into the accounting system can improve accountability and encourage more sustainable waste management practices. The implications of this study suggest that, for MSMEs, the implementation of environmental accounting through simple ecological cost recording can serve as a managerial instrument to improve operational efficiency and strengthen business legitimacy in ecologically vulnerable tourism areas. This study recommends that business actors and policymakers position green accounting as a strategic approach to coastal environmental preservation.